Neonatal Staff Development in Thailand - Prissana Soontornchai (2018)
Our world is shrinking because of computerized linkages and the mobility of society. Information is shared rapidly around the world. Issues surrounding newborn and infant nursing are global. In efforts to acknowledge the international community, each Newborn and Infant Nursing Review issue will feature a column that highlights care related issues from a featured country or region of the world. This article focuses on Thailand. Our guest authors are Prissana Soontornchai and Tipkamon Stitt. Both Prissana and Tipkamon are from Chiang Mai University Hospital and are Regional Network Contacts for the Council of International Neonatal Nurses for Thailand. This month's article focuses on neonatal staff development. © 2009 Elsevier Inc. All rights reserved.